A religião na educação pública brasileira: O papel do ensino religioso no estado de São Paulo - Gomes, Cybelle Pardo Andrade Amaral (2005)
The religion influenced and has been intimately connected to the educational progress throughout the history of Brazil education. Religious Education is compulsory in Brazil public schools. It being a secular and pluralistic country, where there is religious diversity in every sector of society, including in education, obligatoriness of religious education in the public schools violate the laicicity of the State and contrary the Law and Guidelines and Bases of Education (LDB). The Brazilian religious context shows that the religiosity board significantly changed. In the State of São Paulo, the Secretary of Education of the State and UNICAMP - Public Campinas University elaborated a document to guide the secretaries of municipal education. Such a document defends the importance of the Religious Education discipline, and argues that it will help the student in the developing of the exercising of citizenship. The document contemplates themes such as cultural values, cultural plurarity, and religiousness but shows itself contradictory and flawed in the approaching of these subjects. This research discuss the place of Religious Education in public schools of São Paulo, in order to comprehend how the religion influences directly the secular Brazilian society